SEMANTIC AND PRAGMATIC CHALLENGES FACED BY INDONESIAN EFL LEARNERS - Suci, Nur Annisa; Hidayah Tullah. S, Nur; Sato, Maria Rosa Mistika; Syam, Ulfah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The semantic and pragmatic difficulties Indonesian English as a Foreign Language (EFL) learners encounter are examined in this study. Even though a large number of Indonesian EFL students exhibit sufficient grammatical proficiency, they frequently struggle to comprehend contextual meanings and use language correctly in social situations. The purpose of this qualitative descriptive study is to identify significant factors and investigate the semantic and pragmatic difficulties encountered by 20 Indonesian high school EFL students. Semi-structured interviews, classroom observations, and document analysis of students' oral and written tasks were used to gather data, which was then subjected to thematic analysis. The study's findings show that while students possess sufficient grammatical knowledge, they struggle greatly to comprehend language in everyday communication situations. Lexical ambiguity, taking figurative language literally, and doubt regarding the meaning of words in context are the main semantic problems identified. In the meanwhile, pragmatic issues include misinterpreting deixis, misusing politeness techniques, and having trouble comprehending indirect intent in speech acts. The primary causes of these difficulties include first language interference, cultural norm variations, and a lack of exposure to real English interactions. The significance of explicitly combining semantic and pragmatic competences in English language learning is concluded by this study.